Hyphal tip growth and cytoplasmic characters of Conidiobolus coronatus (Zoopagomycota, Entomophthoromycotina). (2nd January 2018) - Fisher, Karen E.; Romberger, Isobel; Lowry, David; Shange, Phakade; Roberson, Robert W.
ABSTRACT: Characteristics of hyphal structure and growth can provide insights into the mechanisms of polarized growth and support investigations of fungal phylogeny. To assist with the resolution of evolutionary relationships of the zygomycetes, the authors used comparative bioimaging methods (light [LM] and transmission electron [TEM] microscopy) to describe selected subcellular characters of hyphal tips of Conidiobolus coronatus . Growing hyphae of C. coronatus contain Spitzenkörper (Spk). Spk are most commonly present in hyphae of Dikarya (Ascomycota and Basidiomycota) and are rarely reported in zygomycete hyphae, which possess an apical vesicle crescent (AVC). Such findings raise questions regarding the evolution of the Spk and its relationship with the AVC. Descriptions of additional subcellular characters (e.g., mitotic-phase spindle pole bodies, cytoplasmic behavior, organelle structure) are also presented.